Experimental Research on Axial Compression of Reinforced Concrete Short Circular Columns Strengthened with Prestressed Semicircular Steel Plates. (23rd November 2021) - Ren, Zhenhua; Shen, Yaqian; Zeng, Xiantao; Sun, Yuantian
Abstract : According to the statistics of relevant departments, the total area of various existing buildings in China is at least 10 billion m 2, of which about one-third of the houses have reached the design life and the safety reserve is insufficient. It is not economical to demolish these houses and rebuild them, and the benefits of new buildings are far less than those of extending the service life of old buildings through reinforcement. Therefore, reinforcement technology is increasingly indispensable. Currently varying methods for the prestressed reinforcement of concrete columns are developed, but they are generally not practical. Strengthening concrete columns with prestressed semicircular steel plate is a new prestressed strengthening technology. In this article, the experimental study on the axial compression of a reinforced concrete circular section short column strengthened with prestressed semicircular steel plate is carried out by combining experimental and numerical simulation methods, and the calculation formula of the bearing capacity of the reinforced short column is established by finite element analysis.